Entre noésis et praxis: le renouveau de la prise de parole poétique en RDC au début du nouveau millénaire (Altre Modernità, 2016)
Flourishing quantitatively and qualitatively in the early 60s, the poetic production of the DRC experienced a crisis until the end of the Mobutu era. In the fiftieth anniversary of independence, poetry seems to refresh around the themes of homeland and its reconstruction. The reflections proposed in these pages are not limited to the presentation of some Congolese intellectuals and their works - poets, filmmakers and musicians who live in the country or elsewhere, speaking in French, but also in some local or world languages. The intention is rather to show how Congolese poetry in the recent years invites to a mental decolonization and an anti-systemic utopian project.